FAKTOR SELF EFFICACY DAN SAFETY BEHAVIOR PADA PEKERJA LAPANGAN PT. PERTAMINA (Persero) TBBM SEMARANG GROUP - Gheril Pranita Renja Pakas; Kismi Mubarokah (Lambung Mangkurat, 2019)
The initial survey in PT. Pertamina (Persero) TBBM Semarang Group by observations among workers was not using personal protective equipment completely and having unsafe work that risky to have work accident. The ability themselves influenced safety or unsafety behavior among workers. The study aims to analyze the difference of ability and practice of field workers PT. Pertamina (Persero) TBBM Semarang Group on safety behavior before and after exposure of video. This study was a quasi-experimental method pretest-posttest group with video exposure. Forty field worker were interviewed, then analyzed by Wilcoxon. The result showed that respondent’s characteristic was male and the age 22-59 years old. Most respondents had finished high school (70%) and the work period was one year and married (80%). The statistical test results there is a significant difference before and after exposure of video. The probability values of ability and practice variables of 0.000 (<0.05) which mean that there are significant differences on variables. The increase in the average pretest value of self-ability 19,400 to 21,875 (posttest) and practice variables with an average pretest increase of 17,175 to 20,025 (posttest). There was no significant correlation between two variables self-efficacy and safety behavior (p. 0.204. (Mean of Self Efficacy: 21,875 and Mean of Safety Behavior: 20,025). The media which was exposed to the respondent effective to increase self-efficacy and safety behavior.